Odpowiedzi

  • Roma
  • Community Manager
2010-02-09T16:43:15+01:00
A = x - 1
B = 3x + 5
C = 2x - 4

a)
A + B + C = x - 1 + 3x + 5 + 2x - 4 = 6x
b)
A - B - C = x - 1 - 3x - 5 - 2x + 4 = - 4x - 2
c)
(A + B) - C = (x - 1 + 3x + 5) - 2x + 4 = 4x + 4 - 2x + 4 = 2x + 8
d)
A - (B + C) = x - 1 - (3x + 5 + 2x - 4) = x - 1 - (5x + 1) = x - 1 - 5x - 1 = - 4x - 2
e)
(A + B) + C = (x - 1 + 3x + 5) + 2x - 4 = (4x + 4) + 2x - 4 = 4x + 4 + 2x - 4 = 6x
f)
2A + 2B - C = 2*(x - 1) + 2*(3x + 5) - 2x + 4 = 2x - 2 + 6x + 10 - 2x + 4 = 6x + 12